Efektifitas Penggunaan E-Book untuk Melatih Kemampuan Berpikir Kritis Peserta Didik - Rosmawati, Wiwin (Jurnal Didaktika Pendidikan Dasar, 2023)
Critical thinking skills are very important abilities in the learning process that need to be possessed. Critical thinking is one of the innovation skills needed in the 21st century to prepare graduates who are able to compete in the job market. By using appropriate and interesting learning media, reading will no longer be boring. One way to develop critical thinking skills is to utilize teaching materials in the learning process. These teaching materials include interactive e-books. Interactive e-books are used as a student-centered learning resource; they can be used independently, because the teaching materials which contain interesting and interactive content and student worksheets will be able to stimulate children to think critically and creatively. By using e-books to train students' critical thinking skills. This research aims to determine the effectiveness of using e-books to train students' critical thinking skills. Type of research This research is library research using the literature study research method. Data analysis This research uses qualitative descriptive analysis. The results of this research are that the use of e-books can effectively train students' critical thinking skills.